Evaluation of residual stresses in carbon/carbon composites components joined to copper before and after pulse electromagnetic treatment - Stepanov, G. V.; Babutskii, A. I.; Mameev, I. A.; Ferraris, M.; Casalegno, V.; Salvo, M. (Strength of materials, 2011)
Results of experimental and calculated evaluation of residual stresses in carbon/carbon composites components produced by joining of carbon fiber reinforced carbon composites to copper are presented. Pulse electromagnetic field treatment of the joint was found to decrease its residual stresses.